Islam in the Hinterlands: Muslim Cultural Politics in Canada By Jasmine Zine, ed. (Vancouver, Canada: University of British Columbia Press, 2012. 325 pages.) (American Journal of Islam and Society, 2014)
There have been few studies on Islam in Canada. Hence this publication is awelcome addition to the list. Its ten chapters, divided into four sections, examinediverse issues regarding Muslim cultural politics in the Canadian hinterlands.More specifically, it seeks to understand how they have been affectedby the post-9/11 era of wars, domestic security policies, calls for reformation,and media sensationalism, as well as how these, combined with racial and re-ligious profiling, have impacted Muslims in the Canadian diaspora. The booktries to construct multiple readings of Islam and Muslims by examining thiscommunity within its social, cultural, educational, and political settings andthe integration of these diverse factors in the formation of the national Islamicmosaic.The first section covers gender, race, the Shari‘ah debate, and Muslimwomen’s political engagement. Section 2 focusses on media representationand examines the construction of the “Muslim other” post-9/11, the politicsof reform as articulated by two Muslim female journalists, and the representationof Canadian Islam in a popular Muslim sitcom. An important theme insection 3 is the civic engagement of the country’s Islamic schools. The lastsection looks at security issues and the targeting and profiling of Muslims inpost-9/11 Canada.As Jasmine Zine correctly points out in the introduction, Muslims havebeen living peacefully in Canada since the middle of the nineteenth centuryand are proud to be Canadian. However, since 9/11 the debate on their integrationinto the mosaic and their appropriation of Canadian values has intensified,especially in Quebec, where discrimination and prejudice haveincreased due to the issue of veiling. Women who choose to veil are exiledfrom public services and space by means of Bill 94. In essence they are portrayedas victims of patriarchal violence ...